EFFECT OF MEDIA, BENZYL ADENINE, AND NPK FERTILIZER ON THE GROWTH AND DEVELOPMENT OF OXALIS (Oxalis triangularis) PLANT - KHUSHABA, BAN G.; EDO , NASHWAN Y.; HASAN, JIHAD Y. (Journal of Duhok University, 2022)
The present study was conducted in a plastic house in the campus of Duhok university, Kurdistan region, Iraq, during the growing year 2021, to investigate the effect of different factors includes growing media (river soil, peatmoss and river soil + peatmoss 1:1), Benzyl Adenine (BA) (0 and 500 mg.l-1), NPK fertilizer (0, and 200 mg.l-1) per pots on the growth of oxalis plant (Oxalis triangularis). The results showed that the peatmoss significantly improved all the studied parameters compared with mixture and river soil. Similarly, benzyl adenine at (500 mg.l-1) increases most study characters except rhizomes number, single rhizome volume and single rhizome fresh weight. However, NPK fertilizer at concentration (200 mg.l-1) per pot improved leaf length. The interactions between peatmoss and (500 mg.l-1) BA recorded significantly entire growth measurements exclude rhizomes number, single rhizome volume and single rhizome fresh weight. Whereas, the interactions between peatmoss and without NPK fertilizer, positively enhanced leaf number, vegetative dry weight, rhizomes number, and single rhizome volume, also the interactions of (500 mg.l-1) BA plus (200 mg.l-1) NPK leading to encourages most parameters in the research. And the triple interaction among peatmoss, (200 mg.l-1) NPK and (500 mg.l-1) BA recorded best results of most studied parameters